Beginning Web Development, Silverlight, and ASP.NET AJAX From Novice to Professional - Moroney, Laurence (Apress : Imprint: Apress, 2008)
Beginning Web Development, Silverlight, and ASP.NET AJAX: From Novice to Professional aims to give you the skills you need to start building web applications with Microsoft's next-generation technology as quickly as possible. Whether you're interested in ASP.NET AJAX, Silverlight, or the technologies that support them (WPF, WCF, WF, etc.), this book is the starting point that you need. It adopts a "zero to hero" approach that concentrates on achieving practical results you can use in real projects rather than presenting a deep academic treatment that can't be immediately applied. The aim is to give you, the reader, the knowledge you need to achieve the results you want with the minimum of fuss. When you've read this book, you'll have a solid understand of all the techniques that are available, when to use them, and their relative strengths and weaknesses.